Cartilage Damage Pathological Characteristics of Diabetic Neuropathic Osteoarthropathy - Pei-Long Liu; Jia-Yu Diao; Qiong Wang; Huan Liu; Yan Zhang; Jing-Qi Liang; Feng Zhang; Xiao-Jun Liang; Hong-Mou Zhao (Analytical Cellular Pathology)
Background. Diabetic neuropathic osteoarthropathy (DNOAP) is a rare and easily missed complication for diabetes that leads to increased morbidity and mortality. DNOAP is characterized by progressive destruction of bone and joint, but its pathogenesis remains elusive. We herein aimed to investigate the pathological features and pathogenesis of the cartilages damage in DNOAP patients. Methods. The articular cartilages of eight patients with DNOAP and eight normal controls were included. Masson staining and safranine O/fixed green staining (S-O) were used to observe the histopathological characteristics of cartilage. The ultrastructure and morphology of chondrocytes were detected by electron microscopy and toluidine blue staining. Chondrocytes were isolated from DNOAP group and control group. The expression of receptor activator of nuclear factor kappaB ligand (RANKL), osteoprotegerin (OPG), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and Aggrecan protein was evaluated by western blot. Reactive oxygen species (ROS) levels were measured using a 2′,7′-dichlorofluorescin diacetate (DCFH-DA) probe. The percentage of apoptotic cells was determined by flow cytometry (FCM). The chondrocytes were cultured with different glucose concentrations to observe the expression of RANKL and OPG. Results. Compared with the control group, the DNOAP group showed fewer chondrocytes, subchondral bone hyperplasia, and structural disorder, and a large number of osteoclasts formed in the subchondral bone area. Moreover, mitochondrial and endoplasmic reticulum swellings were observed in the DNOAP chondrocytes. The chromatin was partially broken and concentrated at the edge of nuclear membrane. The ROS fluorescence intensity of chondrocyte in DNOAP group was higher than that in normal control group (28.1±2.3 vs. 11.9±0.7; P<0.05). The expression of RANKL, TNF-α, IL-1β, and IL-6 protein in DNOAP group was higher than that in normal control group, whereas OPG and Aggrecan protein were lower than that in normal control group (both P<0.05). FCM showed that the apoptotic rate of chondrocyte in DNOAP group was higher than that in normal control group (P<0.05). The RANKL/OPG ratio showed significant upward trend when the concentration of glucose was over than 15 mM. Conclusions. DNOAP patients tend to have severe destruction of articular cartilage and collapse of organelle structure including mitochondrion and endoplasm reticulum. Indicators of bone metabolism (RANKL and OPG) and inflammatory cytokines (IL-1β, IL-6, and TNF-α) play an important role in promoting the pathogenesis of DNOAP. The glucose concentration higher than 15 mM made the RANKL/OPG ratio change rapidly.